Analyzing soccer match sprint distances: A comparison of GPS-based absolute and relative thresholds - Silva, Hugo; Nakamura, Fábio Yuzo; Loturco, Irineu; Ribeiro, João; Marcelino, Rui (Biology of Sport, 2024)
This study compared the most common absolute sprint threshold (> 25.2 km/h) with relative and individualized thresholds (> 70%, > 75%, > 80%, > 85% and > 90% of peak match speed). Twenty elite soccer players, competing in the first division of the Portuguese League, were monitored using GNSS equipment during thirty-four official matches. Peak match speed was retrieved as the individual maximal speed reached during the full season. Distances were registered when speed overcame the absolute and the relative thresholds. Mean±SD of peak speeds and distances covered were calculated, and Pearson correlation ( r ) and mean paired differences were performed to analyze relationships and differences between thresholds. The peak match speed was 32.9±1.4 km/h. Correlations between distances covered using the absolute and relative thresholds varied from very strong (> 70%: r = 0.84, p 75%: r = 0.89, p 80%: r = 0.88, p 85%: r = 0.79, p 90%: r = 0.59, p 75% (ES: 0.23 [95% CI: 0.16, 0.31]) and the > 90% (ES: -1.65 [95%CI: -1.85, -1.48]) relative thresholds presented the smallest and largest differences, respectively, with the absolute threshold. Differences were also found when considering the playing positions. While the distances covered by central midfielders were similar between the absolute and > 80% thresholds (-0.03 [-0.16, 0.10]), fullbacks covered largely more distance -1.88 [-2.42 -1.50]) in the absolute threshold than in the > 80% threshold. The distances covered by players varied based on the selected threshold, affecting the distances covered by different playing positions. Being the highest speed threshold within displacements thresholds, the absolute sprint threshold showed greater similarity to lower rather than higher relative thresholds.